Dyeing Performance and Anti-Superbacterial Activity of Cotton Fabrics Dyed with Chamaecyparis obtusa - Na-Young Choi; Bog-Im Park (Molecules, 2023)
In hospitals, doctors’ and patients’ uniforms, as well as bedding and textiles, can be carriers of superbacteria. This study was conducted to test the anti-superbacterial activity of cotton fabrics dyed with extracts of Chamaecyparis obtusa (C. obtusa). The dye was extracted by boiling C. obtusa in water. The test cotton was mordant-dyed three times with the solution at a 1:17 dyeing bath ratio and at an 8.69% (o.w.f) dye concentration for 15 min at 40 °C. C. obtusa dyeing demonstrated a high dyeing affinity in the absence of mordant (K/S value = 14.62). The K/S value of the dyed fabric increased in the order of Cu-mordanted, Fe-mordanted, non-mordanted, and Al-mordanted cotton. Dry cleaning, perspiration and rubbing fastness were determined to be good (Grade 4–5). The dyed fabrics appeared to have a high deodorizing ability compared to the control fabric. They showed not only antibacterial activity against Staphylococcus aureus (S. aureus) and Klebsiella pneumoniae (K. pneumoniae), known to be frequently found in fabrics, but also higher antibacterial activity against the superbacteria methicillin-resistant Staphylococcus aureus (MRSA) (reduced by 99.7%). These results suggest that fabric dyed with C. obtusa extract may be used in clothes and bed linens for inpatients, given its high anti-superbacterial activity. Furthermore, such fabrics may contribute to inhibiting pathogenic infections when used in hospital uniforms or operation gowns for doctors or nurses in hospitals.